PELATIHAN PEMBUATAN PENELITIAN TINDAKAN KELAS (PTK) BAGI GURU-GURU MADRASAH TSANAWIYAH NEGERI (MTsN) TANJUNGBALAI SUMATERA UTARA - Asra Idriyansyah Purba (Jurnal Abdi Mas Adzkia, 2023)
AbstractThe purpose of this community service is to train class action research teachers. The target of this training is teachers at MTsN Tanjungbalai. It is hoped that from this training, teachers will be able to make a class action research to support teacher careers. This training was held for two days which took place in the MTsN Tanjungbalai class, where participants were involved and actively participated in this training. The results showed that there was a change in ability and knowledge to make class action research which was attended by 20 people. This training consists of the following stages: 1. preparation 2. material delivery, 3 mentoring and discussion 4. evaluation of the training activities.